Handing Over the Controls: The Shift from Pilot in Command to Instructor - Diane Erickson (Adult Education Research Conference, 2007)
Certified flight instructors (CFIs) facilitate and assess student pilot learning during each phase of the training required to obtain the private pilot certificate. However, CFIs receive little formal preparation on how to teach. Twenty-two CFIs were interviewed to examine what CFIs know and believe about teaching adult learners.